POLIDEFORMASI PADA BATUAN KELOMPOK EMBALUH-RAJANG DI DAERAH BHAYANGKARA, KALIMANTAN TIMUR - Joko Wahyudiono; Baharuddin Baharuddin (Pusat Survei Geologi, 2011)
The Embaluh-Rajang Group in Bhayangkara region had suffered polyphase deformation. Regional fold shown in Landsat Imagery exhibit at least three periodes of deformation on the study area. The first deformation D1 main principal stress (s11) was directed relatively to east-west and resulted regional folds on the north-south direction. The second deformation D2 main principal stress (s12) was directed relatively to northwest-southeast and formed northeast-southwest trending regional folds. The third deformation D3 main principal stress (s13) was directed relatively to east northeast-west southwest and resulted local folds on the north northwest-south southeast trending direction. Faults occurred in study area could be classified into six main groups. They are fault group of A (north-south), B (north northeast-south southwest), C (northeast-southwest) and D (southeast-northwest), E (south southeast-north northwest).Keywords : polydeformation, fold, fault, regional structure